2021
DOI: 10.1177/03611981211031537
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest Model for Trip End Identification Using Cellular Phone and Points of Interest Data

Abstract: Cellular phone data has been proven to be valuable in the analysis of residents’ travel patterns. Existing studies mostly identify the trip ends through rule-based or clustering algorithms. These methods largely depend on subjective experience and users’ communication behaviors. Moreover, limited by privacy policy, the accuracy of these methods is difficult to assess. In this paper, points of interest data is applied to supplement cellular phone data’s missing information generated by users’ behaviors. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…For example, if a trip is completed "walking-bus-walking," we consider this trip's corresponding mode to be the bus. Te trip end identifcation method designed with the same datasets using in this paper was described in the literature [19]. Tus, this paper focuses on the following steps: identifying the travel mode of each single trip segment.…”
Section: Methodsmentioning
confidence: 99%
“…For example, if a trip is completed "walking-bus-walking," we consider this trip's corresponding mode to be the bus. Te trip end identifcation method designed with the same datasets using in this paper was described in the literature [19]. Tus, this paper focuses on the following steps: identifying the travel mode of each single trip segment.…”
Section: Methodsmentioning
confidence: 99%
“…It is positively correlated with the positioning error of mobile phone data generated at activity locations theoretically. However, the traces generated at different activity locations differ in the spatial distribution [29]. It has been found that the fixed DT setting in the traditional clustering algorithm cannot be well applied to all activity locations at the same time [28, 39].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, with the increase of BS density of mobile communication network and the development of Internet economy, the spatial and temporal resolution of mobile phone data gradually increases. The sampling frequency of mobile phone data has rapidly increased to minute-interval level [29]. Some clustering algorithms have been used to recognise activity locations, addressing the noisy and raw nature of mobile phone data [15].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, existing activity classification schemes mostly rely on hand-crafted features. These features are often complicated and need to be carefully designed and selected for identifying different activity types 10 , which consumes tremendous labors. Moreover, such calibrated models show poor generalizability and receive low inference accuracy when applied to new trajectories.…”
Section: Introductionmentioning
confidence: 99%